Tear Cytokine Levels in Contact Lens Wearers With Acanthamoeba Keratitis. Issue 7 (July 2017) - Carnt, Nicole; Montanez, Vicente M.; Galatowicz, Grazyna; Veli, Neyme; Calder, Virginia
Abstract : Purpose: To determine differences in key tear film cytokines between mild and severe cases of acanthamoeba keratitis (AK) and control contact lens (CL) wearers. Methods: This was a prospective study of CL wearers with AK attending Moorfields Eye Hospital and control CL wearers from the Institute of Optometry, London. Basal tear specimens were collected by 10-μL capillary tubes (BLAUBRAND intraMark, Wertheim, Germany), and tear protein levels were measured with a multiplex magnetic bead array (Luminex 100; Luminex Corporation, Austin, TX) for cytokines interleukin (IL)-1β, IL-6, IL-8, IL-10, IL-17A, IL-17E, IL-17F, IL-22, and interferon gamma and with enzyme-linked immunosorbent assay (Abcam, Cambridge, United Kingdom) for CXCL2. Severe cases of AK were defined as having active infection for over 12 months and at least 1 severe inflammatory event. Results: One hundred and thirty-two tear samples were collected from a total of 61 cases (15 severe and 46 mild–moderate) and 22 controls. IL-8, part of the Toll-like receptor 4 cytokine cascade, was found to be expressed at a detectable level more often in cases of AK than in control CL wearers ( P = 0.003) and in higher concentrations in severe cases than in milder forms of the disease (z = −2.35). IL-22, part of the IL-10 family, and a proinflammatory Th17 cytokine, was detected more often in severe cases than in milder forms of AK ( P < 0.02). Conclusions: Profiling patients with AK during disease shows differences in cytokine levels between severe and milder disease that may inform clinical management. The Toll-like receptor 4 and IL-10/Th17 inflammatory pathways should be included in further investigations of this disease.